Inclusive and differential cross-sections for dilepton tt[bar] production measured in √s = 13 TeV pp collisions with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Rio, Fernando del; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; et al. (Journal of high energy physics, 2023)
Differential and double-differential distributions of kinematic variables of leptons from decays of top-quark pairs (tt[bar]) are measured using the full LHC Run 2 data sample collected with the ATLAS detector. The data were collected at a pp collision energy of √s = 13 TeV and correspond to an integrated luminosity of 140 fb−1. The measurements use events containing an oppositely charged eμ pair and b-tagged jets. The results are compared with predictions from several Monte Carlo generators. While no prediction is found to be consistent with all distributions, a better agreement with measurements of the lepton pT distributions is obtained by reweighting the tt[bar] sample so as to reproduce the top-quark pT distribution from an NNLO calculation. The inclusive top-quark pair production cross-section is measured as well, both in a fiducial region and in the full phase-space. The total inclusive cross-section is found to be σ tt[bar] = 829 +- 1 (stat) +- 13 (syst) +- 8 (lumi) +- 2 (beam) pb, where the uncertainties are due to statistics, systematic effects, the integrated luminosity and the beam energy. This is in excellent agreement with the theoretical expectation.
Veröffentlicht: 17. Juli 2023
*The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, F.L. Castillo, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, S.M. Weber, M. Wessels, L. Vigani, J. Zinsser [und sehr viele weitere Personen]
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol